Expression of Chemokine Receptors on Peripheral Blood T Cells in Children with Chronic Kidney Disease - Maria Szczepańska; Łukasz Sędek; Irena Makulska; Krystyna Szprynger; Bogdan Mazur; Joanna Bulsa; Danuta Zwolińska; Jacek Karpe; Katarzyna Ziora; Tomasz Szczepański (Mediators of Inflammation)
Chemokine receptors play a role in leukocyte recruitment, activation, and maintaining effector functions and regulate adaptive immune response and angiogenesis. The study aimed at flow cytometric analysis of T cell subsets with selected surface chemokine receptors (CCR4, CCR5, CCR7, CXCR3, and CXCR4) or receptor combination in peripheral blood of children with chronic kidney disease (CKD) on hemodialysis (HD). The percentage of T lymphocytes with CD8 and combined CD28,CCR7 expression was higher in HD children. The percentage of T lymphocytes expressing CCR7, CD28,CCR7, and CXCR4,CD8 was increased in children on conservative treatment. Total number (tn) of CXCR4+ cells was reduced in children on hemodialysis. The tn of T CXCR3+ cells was lower in children on conservative treatment. During HD the percentage of T CD4+ cells was higher and of T CXCR3+ lymphocytes was lower after HD session as compared to 15 min of session duration. During HD tn of T cells with expression of CCR4, CCR5, CCR7, CXCR3, and CXCR4 was constant. The alteration of chemokine receptors expression in children with CKD occurs early in the development. Diminished expression of CXCR3, CXCR4 on T cells in patients with CKD on HD might result in impaired inflammatory response. Increased CCR7+ T cell percentage could be responsible for the alteration of migration of cells into secondary lymphatic organs.